Turnaround Strategies and Performance of Kenya Planters Cooperative Union in Nairobi County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
This study sought to establish the influence of turnaround strategies on performance of Kenya Planters Cooperative Union. The specific objectives guiding the study were to assess the influence of restructuring strategy, reorganization strategy, repositioning strategy and diversification strategy on performance of Kenya Planters Cooperative Union. The resource-based view theory, contingency theory, institutional theory, and balanced scorecard theory all served as the study’s guiding theories. The research design used for this study was a descriptive survey. The study’s target population comprised all 815 people who work for the organization. A desired sample size of 268 respondents was reached by proportionate stratified sampling technique. With the aid of semi-structured questionnaires, primary data was gathered. To evaluate quantitative data, descriptive statistics such as mean and standard deviation were used. In the inquiry, two inferential statistics were used: correlation analysis and multiple regression analysis. The study found that Kenya Planters Cooperative Union’s performance was positively and significantly impacted by restructuring strategy, reorganization strategy, repositioning strategy, and diversification strategy. The analysis found that the organization can reduce operating costs for the business and retail network by implementing a restructuring approach. The organization can respond to the financial challenges and pressures it is now experiencing by reorganizing. Based on the study findings, it is recommended that Kenya Planters Cooperative Union should evaluate its strengths and weaknesses by looking at how well and how poorly the current organizational structure accomplishes business goals.